MODELS CONCERNING PREVENTIVE VERIFICATION OF TECHNICAL EQUIPMENT - CÂRLAN M.; CSUZI. I.; COSTEA M. (Journal of Sustainable Energy, 2016)
The paper presents three operative models whose purpose is to improve the practice of preventive maintenance to a wide range of technical installations. Although the calculation criteria are different, the goal is the same: to determine the optimum time between two consecutive preventive interventions. The optimum criteria of these models are: - the maximum share of technical entity operating probabilities, in the case of the Ackoff - Sasieni [1] method; -the optimum time interval for preventive verification depending on the preventive-corrective maintenance costs imposed by the deciding factor, for the AsturioBaldin [2] model; - the minimum number of renewals – preventive and/or corrective maintenance operations [3]